Multiple skeletal muscle metastases from poorly differentiated gastric adenocarcinoma - Koga, Yuki (Surg Case Rep, 2015)
We report here a rare case of gastric carcinoma with multiple intramuscular metastases. A 71-year-old man presented with rapidly evolving swelling of his left thigh and severe pain. Three years earlier, he had undergone neoadjuvant chemotherapy followed by gastrectomy for advanced gastric cancer. A computed tomography scan showed unusual swellings in multiple skeletal muscles with no vessel or bone invasion. Importantly, the affected muscles did not contain distinct masses but were diffusely enlarged. Pathological examination of an open muscle biopsy showed a poorly differentiated adenocarcinoma, supporting a diagnosis of gastric cancer metastases in multiple skeletal muscles.